PENINGKATAN KESANTUNAN BERBAHASA INGGRIS DALAM KOMUNIKASI DARING MELALUI PELATIHAN LITERASI BAHASA BAGI MAHASISWA - Istu Sri Poneni (Cattleya Darmaya Fortuna, 2025)
The rapid growth of online communication among university students has significantly increased the use of English in digital interactions. However, improper language use, lack of politeness strategies, and limited pragmatic awareness often lead to miscommunication and reduced effectiveness in online discourse. This community service program aims to enhance students’ politeness in English online communication through structured language literacy training. The program was implemented using a participatory approach, including socialization sessions, interactive workshops, practical exercises, and guided practice in real online communication contexts. The training focused on politeness strategies, appropriate language use in digital platforms, and awareness of cultural and pragmatic aspects of English communication. The results indicate an improvement in students’ understanding of polite language expressions, increased awareness of digital communication ethics, and enhanced ability to apply polite English in online interactions. This program contributes to fostering respectful, effective, and ethical online communication among students and supports the development of digital literacy in higher education.